2020
DOI: 10.7554/elife.52623
|View full text |Cite
|
Sign up to set email alerts
|

The p75 neurotrophin receptor in AgRP neurons is necessary for homeostatic feeding and food anticipation

Abstract: Networks of neurons control feeding and activity patterns by integrating internal metabolic signals of energy balance with external environmental cues such as time-of-day. Proper circadian alignment of feeding behavior is necessary to prevent metabolic disease, and thus it is imperative that molecular players that maintain neuronal coordination of energy homeostasis are identified. Here, we demonstrate that mice lacking the p75 neurotrophin receptor, p75NTR, decrease their feeding and food anticipatory behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…There are a few crucial molecular signals and receptors in the ARC that are essential to mediating feeding and appear to be involved in FAA. A recent study identified a circadian role for the neurotrophin receptor p75NTR activity in AgRP neurons in driving FAA [ 99 ]. p75NTR is a brain-derived neurotrophic-factor (BDNF) receptor that rhythmically mediates oscillation of certain metabolic liver genes [ 100 ].…”
Section: A Regulatory Role For Hypothalamic Clocks In Feeding and mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few crucial molecular signals and receptors in the ARC that are essential to mediating feeding and appear to be involved in FAA. A recent study identified a circadian role for the neurotrophin receptor p75NTR activity in AgRP neurons in driving FAA [ 99 ]. p75NTR is a brain-derived neurotrophic-factor (BDNF) receptor that rhythmically mediates oscillation of certain metabolic liver genes [ 100 ].…”
Section: A Regulatory Role For Hypothalamic Clocks In Feeding and mentioning
confidence: 99%
“…p75NTR is a brain-derived neurotrophic-factor (BDNF) receptor that rhythmically mediates oscillation of certain metabolic liver genes [ 100 ]. Mice lacking p75NTR in either the AgRP neurons or the entire brain express FAA only during the active phase, but not the rest phase [ 99 ]. Additionally, the mammalian target of rapamycin (mTOR) protein, highly expressed in the ARC and PVN, is implicated in rhythmic feeding [ 101 , 102 ].…”
Section: A Regulatory Role For Hypothalamic Clocks In Feeding and mentioning
confidence: 99%
“…The underlying neuronal systems and/or circuitry responsible for mediating FAA have been contested, with very few studies showing reproducible effects of genetic mutations or lesions to the brain ( Figure 1 ) ( Davidson, 2009 ; Gunapala et al, 2011 ). At present, nuclei as diverse as the cerebellum ( Mendoza et al, 2010a ) hypothalamic areas including dorsomedial hypothalamus (DMH) ( Mieda et al, 2006 ; Acosta-Galvan et al, 2011 ) and arcuate nucleus ( Podyma et al, 2020 ); and striatum ( Liu et al, 2012 ; Gallardo et al, 2014 ), have been implicated in promoting FAA. The only area of consistent agreement is that the SCN is not required for FAA ( Krieger et al, 1977 ; Stephan et al, 1979 ; Davidson, 2009 ; Takasu et al, 2012 ; Mistlberger, 2020 ), although it might modulate the amplitude of food rhythms in some contexts ( Angeles-Castellanos et al, 2010 ; Fernandez et al, 2020 ).…”
Section: Food As a Zeitgebermentioning
confidence: 99%
“…As p75NTR has been implicated in other metabolic functions regulated by leptin, including feeding and glucose homeostasis, we next assessed whether leptin responsiveness was intact (16,18).…”
Section: Loss Of P75ntr In Leptin-deficient Ob/ob Mice Leads To Obesimentioning
confidence: 99%
“…Similar to the TNFα receptors, p75NTR has been implicated in insulin sensitivity and glucose control in adipocytes, and has also been found to be necessary to promote weight gain on a high fat diet (16,17). Recently, we found that mice lacking p75NTR (Ngfr-KO) exhibit a phenotype of decreased food intake with increased weight loss on TRF, but while maintaining blood glucose levels similar to that of controls (18). However, due to their resistance to dietinduced obesity, it is unknown whether p75NTR may have a role in modulating glucose homeostasis during TRF in the setting of obesity.…”
Section: Introductionmentioning
confidence: 99%